An Infallible Theologian? : Understanding Gregory Nazianzen's Authority in Maximus the Confessor - Summerson, Andrew J. (Journal of early Christian studies, 2025)
Maximus the Confessor discloses his most wide-ranging theological speculations in the genre of commentary, a practice understudied and partially misunderstood. To understand the reasons for this approach, this study draws attention to the techniques of the philosophical commentary tradition with which Maximus engages Gregory Nazianzen. Much like Middle Platonic and Neoplatonic views of Plato, Maximus’s analysis begins with the premise that Gregory is right. This assumption involves interpretive strategies to make sense of authoritative writings. As an authority for Maximus, Gregory’s corpus is internally consistent. Hence, knowledge of his wider corpus clarifies obscure passages. He must also be congruent with the ancient wisdom of scripture. Gregory as “theologian” is subject to the same strategies of allegorical exegesis for deriving meaning from his obscure texts. Last, Gregory as an authority must harmonize with other authorities, such as Dionysius. Maximus’s grappling with Gregory in this manner promotes the coinherence of preaching and metaphysics, the essential elements of Christian theological grammar.